2020
DOI: 10.1038/s41598-020-68804-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of progranulin on the pathological conditions in experimental myocardial infarction model

Abstract: Progranulin is a secreted growth factor associated with multiple physiological functions in ischemic pathophysiology. However, it is still not fully understood how progranulin is involved in ischemic lesion and cardiac remodeling after myocardial infarction (MI). In this study, we investigated the effects of progranulin on myocardial ischemia and reperfusion injury. We investigated progranulin expression using Western blotting and immunostaining after permanent left coronary artery (LCA) occlusion in mice. Inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…8 PGRN has pleiotropic properties by participating inflammatory response, regeneration, cell cycle control, and tissue development. [9][10][11][12] Of interest, PGRN is recently regarded as a crucial regulator to prevent fibrotic process in different diseases, such as liver fibrosis, 13 myocardial infarction 14 and cutaneous wound healing. 15 But the effect of PGRN on house dust mite-induced airway remodeling is still elusive.…”
Section: Introductionmentioning
confidence: 99%
“…8 PGRN has pleiotropic properties by participating inflammatory response, regeneration, cell cycle control, and tissue development. [9][10][11][12] Of interest, PGRN is recently regarded as a crucial regulator to prevent fibrotic process in different diseases, such as liver fibrosis, 13 myocardial infarction 14 and cutaneous wound healing. 15 But the effect of PGRN on house dust mite-induced airway remodeling is still elusive.…”
Section: Introductionmentioning
confidence: 99%
“…PGRN, which is a growth factor also referred to as granulin epithelin precursor, plays a critical role in in ammation and wound repair, and also suppresses in ammation by binding the TNF-α receptor and interrupting TNF-α signaling [16]. In several studies, administration of recombinant PGRN ameliorated renal injury, in ammatory arthritis, myocardial infarction, and acute lung injury [16][17][18][19][20]. The results in the present study showed that rPGRN was less effective than rSLPI in attenuating AA growth in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have shown that PGRN has protective effects on ischemic pathology in the brain and kidney 17,18 . We have also reported that administration of PGRN protects against cardiac injury after MI in mice and rabbits 19 . However, the role of endogenous PGRN in cardiac remodeling after MI remains unclear.…”
Section: Introductionmentioning
confidence: 88%